Eco-Marine-Tourism Development Towards The Renewal of Coastal Communities in Gerokgak District, Bali - Kardi, Cening; Wiasta, I Wayan (E-Journal of Tourism; Volume 7 Number 1 (March 2020)DO - 10.24922/eot.v7i1.58743, 2020)
The environmentally-aware marine tourism research aimed: (1) to analyze the geographical indication for grouper products in Gerokgak district; (2) to analyze the management efforts to guard coastal and marine healthy in the form of customary rule; and (3) to formulate the model for development of Gerokgak coastal eco-marine-tourism. The research method used survey, focus group discussion and laboratory examination. The Grouper aquaculture products both seeds and fishes of Cantang cultivar on the coast of Gerokgak district have been excellent due to the appropriate geographic factors, quality of coastal and marine waters, substrate condition of the seabed and climate and the unique culture of the local community which is identified as Nyegare-Gunung cultivation. The Geographical Indications for Cantang grouper potentially to provide opportunities for fishery producers to consolidate and increase prices on the market. The reputation built around the Geographical Indications can strengthen the product position in the domestic and international markets as well as to penetrate the new export market. The development of eco-marine-tourism in Gerokgak district should control the degradation of environmental quality for grouper aquaculture by creating customary rules of Awig Awig and Subak for coastal villages, and implementation to achieve rationality in utilizing coastal and marine resources harmoniously with the system of values in tradition, religion, aspiration, and culture of the local communities. To keep the reputation of grouper products towards a certification that the product possesses certain qualities, is made according to local integrated marinculture methods, due to Gerokgak’s geographical origin. They should do structuring and developing Bangsal Beach for centre destination to access the sea cage cultivations, as well as Batu Agung Beach as center access to hatchery objects. Marketing tour packages of the activities, products, and landscapes of the grouper marinculture in which the setting up Eco-marine-tourism management should follow open/spontaneous type with the purpose: to grow region merging with the structure of life, both space and patterns in accordance with the local community or community-based tourism. Keywords: Eco-marine-tourism, Grouper, Coastal, Geographical indication